Deciphering sepsis: transforming diagnosis and treatment through systems immunology - Hancock, Robert E. W.; An, Andy; dos Santos, Claudia C.; Lee, Amy H. Y. (Frontiers in Science, 2025)
Sepsis is an abnormal, life-threatening response to infection leading to (multi-)organ dysfunction and failure. Globally it causes ~20% of deaths and most deaths related to severe COVID-19 that shares various molecular features with sepsis. Current treatment approaches (antimicrobials and supportive care) do not address the complexity of sepsis and its mechanistic heterogeneity between patients and within patients over time. Systems immunology methods, including multi-omics (notably RNA-Seq transcriptomics), machine learning, and network biology analysis hold the promise of transforming the management paradigm towards precision approaches. Immune dysfunctions evident very early in sepsis drive the development of novel diagnostic gene expression signatures (e.g. cellular reprogramming) that could inform early therapy. Sepsis patients can now be categorized into "endotypes" based on unique immune dysfunction mechanisms corresponding to varying severity and mortality rates, raising the prospect of endotype-specific diagnostics and patientspecific immune-directed therapy. Longitudinal within-patient analyses are also elucidating mechanisms (including epigenetics) driving differential sepsis trajectories over time, enabling the prospect of disease stage-specific therapy during and after hospitalization, including for post-sepsis and long COVID syndromes. Achieving this transformation will require barriers to systems immunology research to be addressed, including its cost and resourceintensiveness, the relatively low volume of available data, and lack of suitable animal models, and for a change in the mindset of healthcare providers toward precision approaches. This should be prioritized in multi-stakeholder collaborations involving research communities, healthcare providers/systems, and patients and supported by governments, to reduce the high current disease burden from sepsis and to mitigate against future pandemics.